Legitimacy of Non-Formal Constitutional Reforms and Restrictions on Constitutionalism: Legitimasi Perubahan Konstitusi Non-formal dan Pembatasannya dalam Paham Konstitusionalisme - Fajlurrahman Jurdi; Ahmad Yani (Jurnal Konstitusi, 2023)
Non-formal constitutional change through legislative and judicial interpretation raises issues of legitimacy, and restrictions on non-formal changes can be made. This research aims to determine the legitimacy and explore the limitations of non-formal constitutional changes. This research uses normative legal methods with statutory, conceptual and case approaches. The results show that the legitimacy of non-formal constitutional changes is measured based on procedural legitimacy; that is, non-formal changes must be based on authority, and these changes do not affect the meaning of the Constitution as a whole. It is also measured based on substantial legitimacy; namely, non-formal changes to protect human rights. The limitation on changing the non-formal constitution is based on the main substance, which cannot be changed through non-formal changes such as constitutional structure, human rights, restrictions on authority and restrictions based on the moral constitution of the oath of office to implement and enforce the constitution.